Detrital zircon record of rivers' sediments in the North Qilian Orogenic Belt: Implications of the tectonic evolution of the northeastern Tibetan Plateau. (8th August 2018) - Kang, Huan; Chen, Yuelong; Li, Dapeng; Bao, Chuang; Chen, Yawen; Xue, Hua
Abstract : The North Qilian Orogenic Belt (NQOB) is an important element of the northern edge of the Tibetan Plateau, and several rivers run along it. Zircon U–Pb dating, trace elements, and Hf isotopic data derived from the sediments carried by the rivers have been used to deduce the crustal evolution of the NQOB. U–Pb ages obtained from detrital zircons found in the sediments of the Zamu, Zhuanglan, and Beida rivers can be divided into five major age groups, that is, 2, 600–1, 500, 1, 500–1, 100, 1, 100–650, 550–400, and 360–150 Ma, and the corresponding peaks occur at ~2, 450, ~1, 750, ~950, ~450, and ~250 Ma. Archean components, which may be derived from the ancient continental nucleus in the region, are rare in the river sediments. The zircon grains with ages of 360–150 Ma are most likely related to crustal thickening and decompression melting in a post‐collisional tectonic setting. The age distribution patterns indicate that the sediments carried by the Zamu, Zhuanglang, and Beida rivers are derived from the NQOB. Furthermore, the Hf isotopic compositions of Meso‐ and Neoarchean, Mesoproterozoic, Grenvillian, Pan‐African, Caledonian, and Hercynian zircon age groups exhibit a wide range of εHf ( t ) values, suggesting diverse sources. The existence of strongly negative ε Hf ( t ) values among the Grenvillian and Paleoproterozoic zircons indicates that the source magma included reworked Palaeoarchean crustal materials. New results indicate that continental rifting and the opening of the Qilian Ocean occurred at 775–520 Ma; the subduction and closure of the Qilian Ocean occurred at 520–440 Ma; arc–continent collision and continental subduction occurred at 440–420 Ma; and orogen collapse and extension occurred at 400–360 Ma. Our study indicates that the formation of the NQOB was mainly related to the evolutionary history of the Proto‐Tethys Ocean.